Review Implementasi Teknologi Informasi dan Komunikasi dalam Kegiatan Pembelajaran: Studi Kasus SMK di Kota Padang Panjang - Remon Lapisa; Irma Yulia Basri; Milana Milana; Ahmad Arif (Universitas Negeri Padang, 2019)
The implementation of Information and Communication Technology (ICT) into learning activities presents a significant effect on the quality of education, especially in the era of the industrial revolution 4.0. The present study aims to evaluate the level of implementation of ICT in learning activities for vocational teachers. This experimental research used survey method by distributing questionnaires to respondents with different subject expertise.The results showed that the use of ICTs in learning process has not been implemented optimally. This is caused by the low competence of teachers in the sector of information and communication technology. In addition, the lack of ICT infrastructure in schools causes a deceleration in the development of ICT-based learning models. Comprehensive improvement need to be implemented so that the development of ICT-based learnings model can be performed. The results of this study are expected to provide positive feedback to improve the quality of Indonesian education